Effective typification of the name Linum austricum var. collinum (Linaceae), and its synonym L. immaculatae - Ferrer-Gallego, P. Pablo; Martínez Labarga, Juan M. (Phytotaxa, 2022)
The typification of the name Linum austricum subsp. collinum is revisited. The name was “lectotypified” from a specimen kept at BM. This type designation is briefly discussed and superseded because was being contrary to Art. 9.3 of the International Code of Nomenclature for algae, fungi, and plants (Shenzhen Code). In this work, all relevant specimens are carefully evaluated for the purpose to fix the application of the name. We have chosen and designated the best admissible lectotype for this name from the original material. In addition, the lectotype of the name Linum immaculatae, currenty treated as a synonym of Linum austricum subsp. collinum, is designated from a specimen preserved at MA.